Sociological implication of pro parte dolus pro parte culpa form of fault in the formulation of passive money laundering (Research, Society and Development, 2020)
This research determines and analyzes the sociological implications of the provisions of the passive money laundering in Article 5 paragraph (1) of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering formulated in pro parte dolus pro parte culpa form of fault. Normative legal research with the statute and conceptual approaches was used. The results showed that the sociological implication of the formulation of provisions in question is that it can cause state budget overspending for disproportionate interests. With the existence of a large state budget expenditure, especially for the implementation of imprisonment against the criminal act of negligent passive money laundering, the state budget which should be used for the welfare of the community is reduced.